Recent Developments in the Formulation of Nanoliposomal Delivery Systems - Dahiya, Mandeep; Dureja, Harish (Current Nanomaterials, 2018)
Nanoliposomes, or submicron bilayer phospholipid vesicles, are a novel tool to encapsulate and deliver the active pharmaceutical ingredients. The listing of active substances for integration into nanoliposomes is enormous, varying from pharmaceuticals to nutraceuticals and cosmetics. Due to their biocompatible and biodegradable nature, besides their nanosize, nanoliposomes have applications in diverse areas, like cancer nanotherapy, cosmetics, gene delivery and agricultural food technology. Nanoliposomes have the capability of improving the efficacy of active agents by recuperating there in vitro-in vivo solubility, bioavailability, stability and prevent unnecessary interactions between molecules. Targeting by nanoliposomes depends on the types of the cells to achieve active drug concentrations for favorable therapeutic effectiveness at the desired target site and minimizing undesirable effects on healthy tissues and cells. This article sums up the existing studies that have described the nanoliposomal particles as carriers to transport a variety of pharmaceutical agents, properties, methods of preparation, and analysis.
Keywords: magnetic